Interdisciplinary paleovegetation study in the Fernando de Noronha Island (Pernambuco State), northeastern Brazil - Pessenda, Luiz Carlos Ruiz (2008)
The aim of this research was to reconstruct vegetation changes (with climate inferences) that occurred during the Holocene in the Fernando de Noronha Island, Pernambuco State, northeastern Brazil. The research approach included the use of geochemical (mineralogy, elemental), carbon isotopes (δ13C, 14C) and pollen analyses in soil organic matter (SOM) and sediments collected in Lagoa da Viração and Manguezal do Sueste. The carbon isotopes data of SOM indicated that there was no significant vegetation changes during the last 7400 BP, suggesting that the climate was not the determinant factor for the vegetation dynamics. The pollen analysis of the sediment of a core collected in the Lagoa da Viração showed the absence of Quaternary material in the period between 720 BP and 90 BP. The mineralogical analysis of deeper layer showed the presence of diopside indicating this material was developed "in situ". Only in the shallow part of the core were found pollen of similar plant species of the modern vegetation. The geochemistry and isotope results, in association with the sediment type and pollen analyses of sediment samples of Manguezal do Sueste, indicated variations in the vegetation and in its location since the middle Holocene. Such variations can be associated with climatic events and sea level oscillations and also with anthropogenic events considering the last five hundred years._________________________________________________________________________________________ RESUMO: Esta pesquisa teve o objetivo de reconstruir trocas de vegetação (com referências climáticas) que ocorreram durante o Holoceno na ilha de Fernando de Noronha, Estado de Pernambuco, nordeste do Brasil. Para o desenvolvimento da pesquisa utilizou-se de análises geoquímicas (minerais, elementar), isótopos do carbono (δ13C, 14C) e análises polínicas em solos e sedimentos coletados na Lagoa da Viração e no manguezal do Sueste. Os isótopos do carbono dos solos indicaram que não houve trocas significativas de vegetação durante os últimos 7400 anos AP, sugerindo que o clima não foi um fator determinante para a dinâmica da vegetação. A análise polínica dos sedimentos da Lagoa da Viração mostrou ausência de elementos quaternários no período entre 720 AP e 90 AP. A análise mineralógica das camadas mais profundas mostrou a presença de diopsídeo, indicando que este material foi desenvolvido"in situ". Somente na parte superficial do testemunho foram encontrados palinomorfos de plantas similares à vegetação moderna. Os resultados geoquímicos e isotópicos, em associação com o tipo de sedimento e as análises polínicas das amostras de sedimento do Manguezal do Sueste, indicaram variações na vegetação e na sua localização desde o Holoceno médio. Tais variações podem estar associadas a eventos climáticos e oscilações do nível do mar e também a eventos antrópicos considerando os últimos quinhentos anos.